2020
DOI: 10.1007/s10068-020-00819-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-adipogenic effect of Lactobacillus fermentum MG4231 and MG4244 through AMPK pathway in 3T3-L1 preadipocytes

Abstract: This study evaluated the anti-adipogenic effects and mechanisms underlying the action of Lactobacillus fermentum MG4231 and MG4244 strains on adipogenesis and lipid accumulation in 3T3-L1 preadipocytes. Treatment with cell-free extracts (CFEs) from the two strains reduced lipid accumulation and intracellular triglyceride production in 3T3-L1 adipocytes by more than 50%. The inhibitory effects of L. fermentum on lipid accumulation were mediated by the downregulation of FAS and aP2 resulting from the inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…To confirm this antiadipogenic effect, the expression of adipogenesis-related genes was examined by qRT-PCR. Several studies have demonstrated the inhibition of adipogenesis in adipocytes on treatment with functional bacterial strains, which regulate adipogenic transcription factors [35,36]. Similar findings were observed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…To confirm this antiadipogenic effect, the expression of adipogenesis-related genes was examined by qRT-PCR. Several studies have demonstrated the inhibition of adipogenesis in adipocytes on treatment with functional bacterial strains, which regulate adipogenic transcription factors [35,36]. Similar findings were observed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The adhesion ability of LAB was evaluated using HT-29 colorectal cells, as described previously [ 21 ]. HT-29 colorectal cells (1 × 10 5 cells/mL) were incubated in 12-well plates in 5% CO 2 at 37 °C for 24 h. The LAB were cultured in MRS broth at 37 °C for 24 h. The strains were resuspended at 1 × 10 8 CFU/mL in DMEM without FBS and PS and administered to cells.…”
Section: Methodsmentioning
confidence: 99%
“…ND group received a diet containing 14% fat, 21% protein, and 64% carbohydrate (Furina Inc., Seongnam, Korea). Dosages of these strains were established based on results obtained from in vitro preliminary studies (Kim et al, 2020) and those used in previous studies (Hussain et al, 2020;Li et al, 2020).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…In our previous study, two human-derived strains of Limosilactobacillus (formerly Lactobacillus) fermentum MG4231 and MG4244 were isolated. These strains have been shown to inhibit adipocyte differentiation in vitro and have been identified as probiotics candidates Kim et al, 2020). Therefore, this study aimed to evaluate the anti-obesity activity of L. fermentum MG4231, MG4244, and their combination to identify the underlying molecular mechanisms associated with lipid metabolism in a HFD-induced obese mouse model.…”
Section: Introductionmentioning
confidence: 99%